Intentional dehydration of taekwondo practitioners in relation to their stamina and motor skills level - Trojanowska, Izabela Barbara; Wsiaki, Marta; Koźlenia, Dawid; Domaradzki, Jarosław (Journal of Education, Health and Sport, 2018)
Introduction In sports where competitors are divided into weight classes, a problem of obtaining the desired body mass on the competition day occurs. This issue is present primarily in martial arts, with an exception of fencing. Therefore, adjusting body mass is a component of the training process and happens cyclically due to participation in tournaments (Sterkowicz, 2006). These procedures are used most frequently before competitions in order to fit into the limits of a lower or higher weight class (Sterkowicz et al., 2005). Taekwondo tournaments participants are divided into weight classes, just like is wrestling, judo, and other martial arts. The purpose of the division is to ensure fairness of the fights by selecting opponents of similar morphological and physiological characteristics. Nonetheless, decreasing body mass for the purpose of qualifying into the lower weight class is a frequent phenomenon (Janiszewska et al., 2012). A large percentage of the competitors reduces body mass during the short period preceding the official weighting before a tournament, then go back to the natural body mass during the several hours before the tournament starts (Kazemi, 2005; Fleming, 2009). It is possible that the competitors reduce body mass as a result of discarding excessive fat reserves in specific body parts. However, very frequently it is competitors of very low fat body content rapidly reducing body mass before a tournament solely through dehydration, since it is the only way to qualify to the lower weight class (Shirreffs, 2009). Rapid and quick body mass reduction leading to dehydration, however, is not without influence on body functions. Reports on the problem suggest that occurring negative physiological consequences result in motor skill changes. Nonetheless, there are no reports unequivocally naming the type of motor skills connected to dehydration. Thus, the purpose of the paper was to determine the influence of intentional dehydration on the level of the following motor skills: stamina (strength), coordination (simple reaction time and upper limb movement speed), and speed of taekwondo practitioners.